The Impact of Private versus Social Health Insurance on Offered Waiting Times in German Acute Care Hospitals - Christoph Schwierz; Ansgar Wübker; Björn A. Kuchinke (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper shows that patients with private health insurance (PHI) are being offered significantly shorter waiting times than patients with statutory health insurance (SHI) in German acute hospital care. This behavior may be driven by the higher expected profitability of PHI relative to SHI holders. Further,we find that hospitals offering private insurees shorter waiting times as compared to SHI holders have a significantly better financial performance than those abstaining from or with less discrimination.
Keywords: I10; I11; D21; 330; Private health insurance; waiting time; German acute care hospitals; Krankenhaus; Patienten; Kundendienst; Private Krankenversicherung; Gesetzliche Krankenversicherung; Krankenhausfinanzierung; Deutschland